Association between neurosyphilis and diabetes mellitus: Resurgence of an old problem 神经梅毒与糖尿病的关系："旧事"再现. (18th February 2014) - Yang, Tianci; Tong, Manli; Xi, Ya; Guo, Xiaojing; Chen, Yuyan; Zhang, Yafeng; Zhang, Qiao; Liu, Long; Chen, Fuyi; Huang, Songjie; Zhang, Huilin; Zheng, Weihong; et al.
Abstract Background Syphilis, a sexually transmitted disease, is commonly referred to as the "great imitator" because of its wide‐ranging clinical presentations. Recently, we noticed that patients with neurosyphilis (NS) seemed to be more susceptible to complications of diabetes mellitus (DM). This is an interesting phenomenon, but it also puzzles clinicians because of scant knowledge about this situation. Methods A case‐control study was conducted to explore the association between NS and DM. Clinical data and the prevalence of DM among NS patients, patients with syphilis but not NS (syphilis/non‐NS), non‐syphilis patients, and healthy controls were analyzed. In addition, we explored the time of occurrence of NS and DM. Results Fasting plasma glucose and HbA1c levels in NS patients were significantly higher than in syphilis/non‐NS patients, non‐syphilis patients, and healthy controls (P < 0.05). In all, 45 of 149 NS patients (30.2%) were diagnosed with DM. The prevalence of DM in NS patients was significantly higher than in the other three groups (P < 0.05). There was no relationship between the prevalence of DM and the type of NS (e.g. asymptomatic NS, syphilitic meningitis, meningovascular NS, general paresis, and tabes dosalis). In the study population, 57.8% of NS patients were diagnosed with DM at the same time, whereas 80.0% were diagnosed with DM within 5 years of their diagnosis of NS. Conclusions Based on the results of the present study, DM is not merely an occasional chance occurrence in NS patients. There is an association between NS and DM.